Enhanced Cardio Care: Explainable Vision Transformer Multimodal Pipeline For Cardiac Abnormalities Detection Using Electrocardiogram Image Reports - To, Ngoc Minh; Vo, Vu Quoc; Ngo, Quoc Cuong; Kumar, Dinesh Kant; Dinh, Minh Ngoc; Nguyen, Dang Van; Do, Dan Van Buu (Informatica, 2025)
Electrocardiogram (ECG) based Artificial Intelligence (AI) analysis has evolved. Its performance in diagnosing arrhythmias is now comparable to that of human experts, and it has the potential to assist societies with limited healthcare resources. However, these settings often have paper-based ECG image archivesonly, while the current AI-ECG analysis requires digitised ECG signals. To address this, we previously introduced Cardio Care, a mobile-friendly diagnostic pipeline capable of analysing both ECG signals and scanned ECG images. In this extended study, we enhance the pipeline’s explainability and expand its model benchmarking by comparing the Vision Transformer (ViT) with two of its data-efficient variants: DeiT and BEiT. These models were evaluated on two image-based ECG datasets—one public dataset (Mendeley) and one private dataset (Tam Duc Cardiometabolic). Our results show that ViT achieves the strongest classification performance among all three variants, with macro F1-scores of up to 0.99 on Mendeley and 0.81 onTam Duc. Additionally, we integrate a Grad-CAM-based explainability feature to visualise model attention, improving interpretability for clinical use. The enhanced Cardio Care pipeline now has an explainable function using Grad-Cam, demonstrating significant potential for scalable, low-cost cardiac screening inunderserved healthcare settings.